2014
DOI: 10.2478/jppr-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of some synthetic and botanical insecticides on Bemisia tabaci (Hemiptera: Aleyrodidae)

Abstract: In addition to direct mortality caused by insecticides, some biological traits of insects may also be affected by sublethal insecticide doses. In this study, we used the age-stage, two-sex life table method to evaluate the sublethal effects of the four synthetic insecticides: abamectin, imidacloprid, diazinon, and pymetrozin as well as the botanical insecticide taken from Calotropis procera (Asclepiadaceae) extract, on eggs of the cotton whitefly, Bemisia tabaci (Hem.: Aleyrodidae). The lowest and highest surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Additionally, the population prediction results show that an exposure to sub-lethal concentrations of imidacloprid induced M. dirhodum population growth. Similar effects on population growth were observed in an earlier study on sweetpotato whitefly B. tabaci, which proved that imidacloprid Frontiers in Physiology frontiersin.org increases the gross reproduction rate, but does not significantly affect the mean generation time (Esmaeily et al, 2014). Another study involving field experiments in Australian revealed that the egg production and population development of the Australian predatory mite Amblyseius victoriensis (Womersley) significantly increase in response to systemic spray treatments of imidacloprid (James, 1997).…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, the population prediction results show that an exposure to sub-lethal concentrations of imidacloprid induced M. dirhodum population growth. Similar effects on population growth were observed in an earlier study on sweetpotato whitefly B. tabaci, which proved that imidacloprid Frontiers in Physiology frontiersin.org increases the gross reproduction rate, but does not significantly affect the mean generation time (Esmaeily et al, 2014). Another study involving field experiments in Australian revealed that the egg production and population development of the Australian predatory mite Amblyseius victoriensis (Womersley) significantly increase in response to systemic spray treatments of imidacloprid (James, 1997).…”
Section: Discussionsupporting
confidence: 77%
“…Previously, similar effects were documented on the offspring of white-backed planthopper, Sogatella furcifera 29 , cotton aphid, A . gossypii 63 , and brown planthopper, Laodelphax striatellus 64 when subjected to the sublethal concentrations of buprofezin, sulfoxaflor, and thiamethoxam.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are related to reductions in the intrinsic rate of increase ( ri ), finite rate of increase (位), net reproductive rate ( R 0 ), gross reproduction rate ( GRR ) and survival rate. Such effects on offspring growth have also been reported in the cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae) and the small brown planthopper, Laodelphax striatellus (Homoptera: Delphacidae) through treatment with sublethal concentrations of sulfoxaflor and thiamethoxam 39 , 40 . Other insecticides, such as imidacloprid, chlorantraniliprole and triazophos have also lead to significant effects on the life cycle of the white-backed planthopper 23 , 26 , 41 .…”
Section: Discussionmentioning
confidence: 64%
“…Other insecticides, such as imidacloprid, chlorantraniliprole and triazophos have also lead to significant effects on the life cycle of the white-backed planthopper 23 , 26 , 41 . Although imidacloprid significantly affects the GRR in various cases, the generation time ( T ) was not affected in B. tabaci (Hemiptera: Aleyrodidae) 40 . Lashkari et al .…”
Section: Discussionmentioning
confidence: 99%